Steinernema pwaniensis n. sp., a new entomopathogenic nematode (Nematoda: Steinernematidae) from Tanzania - Půža, V; Nermut, J; Mráček, Zdeněk; Gengler, S; Haukeland, S (Journal of Helminthology, 2017)
A new species of entomopathogenic nematode, Steinernema pwaniensis n. sp., belonging to the glaseri group, is described from Tanzania. The infective juveniles of S. pwaniensis n. sp. are characterized by a body length of 978 μm (808-1131), distance from anterior end to excretory pore of 86 μm (80-95) and a tail length of 87 μm (75-95). The ratios a, c and E% of S. pwaniensis n. sp. are substantially lower than those of all other African 'glaseri' group members. The first-generation males of S. pwaniensis n. sp. can be distinguished by a large spicule length of 92 μm (80-97) and by the absence of the caudal mucron, while second-generation males possess a short spine-like mucron. First-generation females have a peg-like tail tip bearing three spine-like projections. Second-generation females can be recognized by a slightly protruding vulva and well-developed post-anal swelling. The new species is further characterized by sequences of the internal transcribed spacer (ITS) and partial 28S regions of the ribosomal DNA. Phylogenetic analyses show that S. pwaniensis n. sp. forms a strongly supported monophyletic clade with two other East African species, S. ethiopiense and S. karii.
Keywords: Animals; biometrie; RNA ribozomální 28S; ribozomální DNA; DNA, Ribosomal; RNA, Ribosomal, 28S; Tanzania; Rhabditida; shluková analýza; anatomické struktury zvířat; Tanzanie; mezerníky ribozomální DNA; DNA, Helminth; Phylogeny; Animal Structures; DNA helmintů; Biometry; Sequence Analysis, DNA; DNA, Ribosomal Spacer; zvířata; sekvenční analýza DNA; Cluster Analysis; mikroskopie; fylogeneze; Microscopy